2020
DOI: 10.1130/b35488.1
|View full text |Cite
|
Sign up to set email alerts
|

On the reconciliation of biostratigraphy and strontium isotope stratigraphy of three southern Californian Plio-Pleistocene formations

Abstract: The San Diego Formation, Pico Formation, Careaga Sandstone, and Foxen Mudstone of southern California are thought to be late Pliocene to early Pleistocene; however, numerical ages have not been determined. Following assessment of diagenetic alteration via multiple methods including scanning electron microscopy (SEM), X-ray diffraction (XRD), and minor elemental concentrations, we attempted to use strontium isotope stratigraphy to assign numerical ages. Using aragonitic fossils, we obtained ages of 2.0−1.85 Ma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Although the numerical age of formations in southern California that span the Plio-Pleistocene boundary remains uncertain due to how the data were originally collected and current refinement of the biostratigraphy, we broke the data down into four-time bins: Holocene (0-11,700 yBP), late Pleistocene (11,700-126,000 yBP), middle Pleistocene (126,000-781,000 yBP), and late Pliocene (~2.6-3.6 Ma) (Fig. 2) (Woodring and Bramlette 1946, Yerkes et al 1965, Bowersox 2005, Buczek et al 2020.…”
Section: Data Acquisition and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the numerical age of formations in southern California that span the Plio-Pleistocene boundary remains uncertain due to how the data were originally collected and current refinement of the biostratigraphy, we broke the data down into four-time bins: Holocene (0-11,700 yBP), late Pleistocene (11,700-126,000 yBP), middle Pleistocene (126,000-781,000 yBP), and late Pliocene (~2.6-3.6 Ma) (Fig. 2) (Woodring and Bramlette 1946, Yerkes et al 1965, Bowersox 2005, Buczek et al 2020.…”
Section: Data Acquisition and Treatmentmentioning
confidence: 99%
“…Lithostratigraphic correlations of rock units within the Los Angeles Basin and San Diego Embayment spanning the Holocene through the Pliocene (modified fromBuczek et al 2020). The age of Pico, Fernando, Niguel and San Diego Formations is heavily debated with estimates ranging from early Pliocene to early Pleistocene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Groves (1991a, b) reported also that the lower Saugus [=Pico] in the Santa Susana Mountains (Valencia area) is Plio-Pleistocene age. Buczek et al (2020) reported that the Pico Fm. in the Valencia area might range into the early Pleistocene.…”
Section: Institutional Abbreviationsmentioning
confidence: 99%
“…The Careaga Sandstone, which crops out in the Santa Marina area of Santa Barbara County in southern California, has been historically regarded as of late Pliocene age. Based on strontium-isotope data (Buczek et al 2020) and the "shifting" of the Pliocene-Pleistocene boundary as dictated by the International Commission of Stratigraphy (see a series of online charts initiated by Cohen et al 2009), the age of the Careaga Sandstone and its rich molluscan content has now been assigned an early Pleistocene age. Such an age would normally exclude any molluscan fauna from being included in this current checklist.…”
Section: Institutional Abbreviationsmentioning
confidence: 99%